PELATIHAN CANVA SEBAGAI MEDIA PEMBUATAN DESAIN MATERI PRESENTASI PADA SISWA SMP NEGRI 1 WODOSARI - Muhammad Didin Febriansyah; Zaehol Fatah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
In the current digital era, visual communication skills have become a crucial competence in education, particularly for junior high school students. However, many students at SMP Negeri 1 Wodosari still face obstacles in developing engaging, interactive, and effective presentation materials due to a limited understanding of modern design software and the basic principles of visual aesthetics. This community service activity aims to enhance students' skills in designing creative and professional presentation media through intensive training on utilizing the cloud-based platform, Canva. The methods employed in this program consisted of three systematic main stages: conceptual lectures on the basic principles of graphic design and an introduction to Canva’s features, hands-on workshops for independent presentation slide creation, and an evaluation of students' work through presentation simulation sessions. The results of the activity demonstrated a significant increase in students' digital literacy and technical design skills. Prior to the training program, the majority of students relied solely on monotonous and unengaging default templates. Post-training, students proved capable of harmoniously exploring visual elements, typography combinations, color usage, and layouts. The presentation products generated by the students exhibited a high level of creativity and strong alignment with the educational content. In conclusion, this training activity successfully optimized the students' creative potential and proved that the Canva platform is an effective, adaptive, and user-friendly medium to support interactive and communicative learning processes at the junior high school level. These findings recommend the importance of integrating similar digital literacy training sustainably into the school's extracurricular curriculum.